PEST ARMYWORMS (Spodoptera frugiperda) ON CORN PLANTS (Zea mays L.) - Brayen Silap; Caroulus S. Rante (Jurnal Agroekoteknologi Terapan, 2021)
Corn (Zea mays L.) is the main food commodity after the rice has a strategic role in the development of agriculture and the economy. The development of this commodity contributes to the provision of foodstuffs and industrial raw materials. The development of corn on a wider scale can potentially increase the income of farmers and the regional economy. Corn is a source of food, carbohydrates, and protein. Corn has the potential as an alternative food substitute for rice.Keywords: corn., pests., commodities. AbstrakJagung (Zea mays L.) merupakan komoditas pangan utama setelah padi yang mempunyai peranan strategis untuk pembangunan pertanian dan perekonomian. Pengembangan komoditas ini berkontribusi dalam penyediaan bahan pangan dan bahan baku industri. Pengembangan jagung dalam skala yang lebih luas dapat berpotensi meningkatkan pendapatan petani dan perekonomian daerah. Unsur gizi pada jagung merupakan sumber bahan pangan, karbohidrat dan protein. Jagung berpotensi sebagai bahan pangan alternatif pengganti padi.Kata kunci : jagung., hama., komoditas.